Arterial site selection for measurement of mean arterial pressure in septic shock patients on high-dose norepinephrine - Bhaskar, Bhanuprakash; Gurjar, Mohan; Mishra, Prabhaker; Azim, Afzal; Poddar, Banani; Baronia, Arvind K. (Frontiers in Medicine, 2022)
Background The Surviving Sepsis Campaign guideline suggests using invasive blood pressure (IBP) measurement in septic shock patients, without specifying arterial site selection for accuracy in relation to the severity of septic shock. The objective of this study was to determine the mean arterial pressure (MAP) gradient between femoral and radial artery sites in septic shock patients. Method This prospective study was done at a 20-bed ICU of a university hospital. The simultaneous MAP measurements at femoral and radial arterial sites were done in septic shock patients receiving norepinephrine (≥0.1 µg/kg/min) with pre-planned analysis for those receiving a high dose of norepinephrine (≥0.3 µg/kg/min). Results The median norepinephrine dose in all 80 studied patients was 0.4 (0.28-0.7) mcg/kg/min, including 59 patients on a high dose of norepinephrine. In all, MAP (mmHg) measured simultaneously at femoral and radial arterial sites showed the mean (95% CI) MAP of 81 (79-83) and 78 (76-80) respectively, with a mean difference of 3.3 (2.67-3.93) p<0.001. In Bland-Altman analysis for MAP, the detected effect sizes were 1.14 and 1.04 for the overall and high dose cohorts, respectively, which indicates a significant difference in the measurement between the two arterial sites. The Pearson coefficient showed a statistically weak correlation between the MAP gradient and the norepinephrine dose among patients receiving a high dose of norepinephrine (r=0.289; p=0.026; 95% CI 0.036-0.508). Conclusion In septic shock patients, MAP measurement was higher at femoral site than at the radial site, particularly in those who received high dose of norepinephrine. Trial Registration Number ClinicalTrials.gov Identifier: NCT03475667